Development, motivation, change – educators’ opinions about groups for teachers on Facebook - Michniuk, Anna (Kultura-Społeczeństwo-Edukacja, 2021)
The aim of the article is to describe support that can be observed in online Facebook teachers’ groups created and administered by teachers or institutions connected with education. The author presented selected Facebook groups, indicated their aims and activities undertaken in their space. On the basis of the conducted research (n = 548), the article will also discuss teachers’ motivations for joining the groups and their reflections connected with belonging to them.